2018
DOI: 10.1177/0091450918774918
|View full text |Cite
|
Sign up to set email alerts
|

When the Brain Leaves the Scanner and Enters the Clinic

Abstract: Addiction neuroscience promises to uncover the neural basis of addiction by mapping changes in the "diseased brains" of people with "drug addictions." It hopes to offer revolutionary treatments for addiction and reduce the stigma experienced by those seeking treatment for a medical, rather than moral, condition. While the promises of addiction neuroscience have received considerable attention, relatively few studies have examined how neuroscientific discourses and promises play out in drug treatment settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The AOD sector has employed a more "medical" approach (Humphreys et al 2005), focused on the individual (rather than broader societal factors), and seeking to reduce the stigma of addiction by framing it as a disease or disorder. One study examining the discourse of Victorian AOD treatment providers found that they tended to alleviate the guilt and shame of substance abusers by referring to the "diseased" or "hijacked" brain (Barnett et al 2018). This "medical" model of addiction as disease or disorder can be seen as allowing men to shift responsibility for violence.…”
Section: Differences Between the Alcohol And Other Drugs And Family Vmentioning
confidence: 99%
“…The AOD sector has employed a more "medical" approach (Humphreys et al 2005), focused on the individual (rather than broader societal factors), and seeking to reduce the stigma of addiction by framing it as a disease or disorder. One study examining the discourse of Victorian AOD treatment providers found that they tended to alleviate the guilt and shame of substance abusers by referring to the "diseased" or "hijacked" brain (Barnett et al 2018). This "medical" model of addiction as disease or disorder can be seen as allowing men to shift responsibility for violence.…”
Section: Differences Between the Alcohol And Other Drugs And Family Vmentioning
confidence: 99%